Calculus: Early Transcendentals, by Anton, 7th Edition,ch03

Calculus - Early Transcendentals

Info iconThis preview shows pages 1–4. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 70 CHAPTER 3 The Derivative EXERCISE SET 3.1 1. (a) m tan = (50 − 10) / (15 − 5) = 40 / 10 = 4 m/s (b) t (s) 4 10 20 v (m/s) 2. (a) (10 − 10) / (3 − 0) = 0 cm/s (b) t = 0, t = 2, and t = 4 . 2 (horizontal tangent line) (c) maximum: t = 1 (slope > 0) minimum: t = 3 (slope < 0) (d) (3 − 18) / (4 − 2) = − 7 . 5 cm/s (slope of estimated tangent line to curve at t = 3) 3. From the figure: t s t t 1 t 2 (a) The particle is moving faster at time t because the slope of the tangent to the curve at t is greater than that at t 2 . (b) The initial velocity is 0 because the slope of a horizontal line is 0. (c) The particle is speeding up because the slope increases as t increases from t to t 1 . (d) The particle is slowing down because the slope decreases as t increases from t 1 to t 2 . 4. t s t t 1 5. It is a straight line with slope equal to the velocity. 6. (a) decreasing (slope of tangent line decreases with increasing time) (b) increasing (slope of tangent line increases with increasing time) (c) increasing (slope of tangent line increases with increasing time) (d) decreasing (slope of tangent line decreases with increasing time) 7. (a) m sec = f (4) − f (3) 4 − 3 = (4) 2 / 2 − (3) 2 / 2 1 = 7 2 (b) m tan = lim x 1 → 3 f ( x 1 ) − f (3) x 1 − 3 = lim x 1 → 3 x 2 1 / 2 − 9 / 2 x 1 − 3 = lim x 1 → 3 x 2 1 − 9 2( x 1 − 3) = lim x 1 → 3 ( x 1 + 3)( x 1 − 3) 2( x 1 − 3) = lim x 1 → 3 x 1 + 3 2 = 3 Exercise Set 3.1 71 (c) m tan = lim x 1 → x f ( x 1 ) − f ( x ) x 1 − x = lim x 1 → x x 2 1 / 2 − x 2 / 2 x 1 − x = lim x 1 → x x 2 1 − x 2 2( x 1 − x ) = lim x 1 → x x 1 + x 2 = x (d) x y Tangent Secant 5 10 8. (a) m sec = f (2) − f (1) 2 − 1 = 2 3 − 1 3 1 = 7 (b) m tan = lim x 1 → 1 f ( x 1 ) − f (1) x 1 − 1 = lim x 1 → 1 x 3 1 − 1 x 1 − 1 = lim x 1 → 1 ( x 1 − 1)( x 2 1 + x 1 + 1) x 1 − 1 = lim x 1 → 1 ( x 2 1 + x 1 + 1) = 3 (c) m tan = lim x 1 → x f ( x 1 ) − f ( x ) x 1 − x = lim x 1 → x x 3 1 − x 3 x 1 − x = lim x 1 → x ( x 2 1 + x 1 x + x 2 ) = 3 x 2 (d) x y Secant Tangent 5 9 9. (a) m sec = f (3) − f (2) 3 − 2 = 1 / 3 − 1 / 2 1 = − 1 6 (b) m tan = lim x 1 → 2 f ( x 1 ) − f (2) x 1 − 2 = lim x 1 → 2 1 /x 1 − 1 / 2 x 1 − 2 = lim x 1 → 2 2 − x 1 2 x 1 ( x 1 − 2) = lim x 1 → 2 − 1 2 x 1 = − 1 4 (c) m tan = lim x 1 → x f ( x 1 ) − f ( x ) x 1 − x = lim x 1 → x 1 /x 1 − 1 /x x 1 − x = lim x 1 → x x − x 1 x x 1 ( x 1 − x ) = lim x 1 → x − 1 x x 1 = − 1 x 2 (d) x y Secant Tangent 1 4 10. (a) m sec = f (2) − f (1) 2 − 1 = 1 / 4 − 1 1 = − 3 4 (b) m tan = lim x 1 → 1 f ( x 1 ) − f (1) x 1 − 1 = lim x 1 → 1 1 /x 2 1 − 1 x 1 − 1 = lim x 1 → 1 1 − x 2 1 x 2 1 ( x 1 − 1) = lim x 1 → 1 − ( x 1 + 1) x 2 1 = − 2 72 Chapter 3 (c) m tan = lim x 1 → x f ( x 1 ) − f ( x ) x 1 − x = lim x 1 → x 1 /x 2 1 − 1 /x 2 x 1 − x = lim x 1 → x x 2 − x 2 1 x 2 x 2 1 ( x 1 − x ) = lim...
View Full Document

Page1 / 52

Calculus: Early Transcendentals, by Anton, 7th Edition,ch03...

This preview shows document pages 1 - 4. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online